An assessment of the critical strains which can be sustained by a mar-ageing steel under bi-axial tension - Pearce, Roger (College of Aeronautics, 1966)
Mar-ageing steels are being specified more and more in advanced engineering applications, and, frequently, the components are manufactured from sheet material. Consequently, the evaluation of the sheet forming properties of this material is of paramount importance; this investigation forms part of this general program. The aim here is two-fold, firstly, to determine the maximum strain which can be sustained under bi-axial stress, and secondly, to suggest any way in which this value can be increased.